An Investigation of Proton Conductivity of Vinyltriazole-Grafted PVDF Proton Exchange Membranes Prepared via Photoinduced Grafting - Sinan Sezgin; Deniz Sinirlioglu; Ali Ekrem Muftuoglu; Ayhan Bozkurt (Journal of Chemistry)
Proton exchange membrane fuel cells (PEMFCs) are considered to be a promising technology for clean and efficient power generation in the twenty-first century. In this study, high performance of poly(vinylidene fluoride) (PVDF) and proton conductivity of poly(1-vinyl-1,2,4-triazole) (PVTri) were combined in a graft copolymer, PVDF-g-PVTri, by the polymerization of 1-vinyl-1,2,4-triazole on a PVDF based matrix under UV light in one step. The polymers were doped with triflic acid (TA) at different stoichiometric ratios with respect to triazole units and the anhydrous polymer electrolyte membranes were prepared. All samples were characterized by FTIR and 1H-NMR spectroscopies. Their thermal properties were examined by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). TGA demonstrated that the PVDF-g-PVTri and PVDF-g-PVTri-(TA)x membranes were thermally stable up to 390°C and 330°C, respectively. NMR and energy dispersive X-ray spectroscopy (EDS) results demonstrated that PVDF-g-PVTri was successfully synthesized with a degree of grafting of 21%. PVDF-g-PVTri-(TA)3 showed a maximum proton conductivity of 6×10-3 Scm−1 at 150°C and anhydrous conditions. CV study illustrated that electrochemical stability domain for PVDF-g-PVTri-(TA)3 extended over 4.0 V.